NILAI AMANAH DAN TAWADU’ BAGI PARA PROFESIONAL PERPUSTAKAAN DAN INFORMASI DARI SUDUT PANDANG ISLAM - Jamal, Johari (UIN Imam Bonjol Padang, 2023)
The purpose of this article is to study the value of two important attributes of librarians, trust and humility from an Islamic view. Introducing some of the ethics that librarians, especially Muslim librarians, must have to provide excellent service to their users, and also to demonstrate the importance of skills in managing an efficient relationship between librarians and users. This article explains the value of trust and humility through studying some relevant verses from the Quran and Hadith of the Prophet Muhammad as well as the sayings of the Imam. Results: This article shows that the two issues discussed have common value in library and information science with an emphasis on Islamic aspects. The newly developed Islamic library and information code of conduct and the proposed method of implementation can be utilized by organizations to their advantage. This study can also help librarians, especially Muslims, to provide better service to library users.